THE ROLE OF WOMEN'S EMPOWERMENT AND CHILD PROTECTION (DP3A) SUKABUMI REGENCY IN OVERCOMING CHILD MARRIAGE CASES IN SUKABUMI DISTRICT - Sintia Nofitri; M. Rijal Amirulloh; Rizki Hegia Sampurna (DIA: Jurnal Administrasi Publik, 2023)
The role of the Sukabumi Regency Women's Empowerment and Child Protection Service (DP3A) in dealing with cases of child marriage in Sukabumi Regency. The purpose of this research is to find out and describe the role of the Sukabumi Regency Women's Empowerment and Child Protection Service (DP3A) in overcoming cases of child marriage in Sukabumi Regency and the inhibiting factors in its implementation. This is motivated by the large number of requests for dispensation letters of introduction to marriage to the P2TP2A Office of Sukabumi Regency in 2021 and the increasing number of child marriages in Sukabumi Regency in the 2020-2021 range. This study used qualitative research methods. Informants in this study were the Office of Women's Empowerment and Child Protection (DP3A) of Sukabumi Regency, P2TP2A of Sukabumi Regency, as well as the community/children who practice child marriage. Data validation in this study used source triangulation and technical triangulation methods. The results of this study are that there are still obstacles for the Sukabumi Regency Women's Empowerment and Child Protection Office in handling child marriage cases, namelythere is a wrong opinion/view of some people that it is a shame if they don't quickly marry off their daughters and there are betel marriages (underhanded) and without being reported.